2011
DOI: 10.1021/ja109160a
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Structural Rearrangements in Porous Coordination Networks

Abstract: With the use of ab initio X-ray powder diffraction, a family of isostructural crystalline porous coordination networks, [(ZnX(2))(3)(TPT)(2)](n)· (solvent) (X = I, Br, Cl), has been studied at elevated temperatures of 573-723 K. Upon heating, all three networks exhibited crystalline-to-amorphous-to-crystalline (CAC) phase transformations to three new networks, [(ZnI(2))(3)(TPT)(2)](n), [(ZnBr(2))(3)(TPT)(2)](n)·(H(2)O) and [(ZnBr(2))(μ-Br)(ZnBr)(TPT)](n), and [(ZnCl(2))(μ-Cl)(ZnCl)(TPT)](n), respectively. A se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 42 publications
1
54
0
Order By: Relevance
“…[a] Under influence of the solvent the crystals converted into a different non‐porous structure: refcode IZUVAB in the CSD. [b] RUM‐3 finally decomposes in pure water, but did allow for the elucidation of ϵ ‐caprolactam, which was introduced from an aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…[a] Under influence of the solvent the crystals converted into a different non‐porous structure: refcode IZUVAB in the CSD. [b] RUM‐3 finally decomposes in pure water, but did allow for the elucidation of ϵ ‐caprolactam, which was introduced from an aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 These features can be used for many applications, e.g. as a crystalline molecular flask in which unstable species can be encapsulated and analyzed by crystallography.…”
mentioning
confidence: 99%
“…We demonstrated that it is possible to perform ab initio powder structure determination of porous coordination networks using low resolution data; totally different coordination networks can be selectively prepared from the same starting materials by thermodynamic and kinetic control; a robust porous coordination network can be prepared from the kinetic product which can be prepared instantly and in a large scale. [1][2][3][4][5] We also demonstrated that a pore in porous networks can be used as a crystalline molecular flask. 6 The robust networks maintain crystallinity and enable direct observation of unstable species by X-ray diffraction.…”
mentioning
confidence: 76%